Impact of smoking on the age at diagnosis of upper tract urothelial carcinoma: Subanalysis of the Japanese Urological Association multi‐institutional national database. (4th August 2015) - Miyazaki, Jun; Nishiyama, Hiroyuki; Fujimoto, Hiroyuki; Ohyama, Chikara; Koie, Takuya; Hinotsu, Shiro; Kikuchi, Eiji; Sakura, Mizuaki; Inokuchi, Junichi; Hara, Tomohiko; the Cancer Registration Committee of the Japanese Urological Association; Kanayama, Hiroomi; et al.
<x xml:space="preserve">Abstract</x> Objectives To examine the influence of smoking history on the diagnosis and other tumor characteristics of upper tract urothelial carcinoma in Japan. Methods A total of 1509 patients with upper tract urothelial carcinoma who were diagnosed in 2005 from 348 Japanese institutions were registered using the multi‐institutional national database of the Japanese Urological Association and included in this analysis. Clinical data of the patients were collected in 2011. The associations between the patients' self‐reported smoking history and their age at the diagnosis of upper tract urothelial carcinoma, sex, pathological T stage and tumor grade were analyzed. Results The mean age at the diagnosis of upper tract urothelial carcinoma was approximately 5 years earlier for the 238 current smokers than for the 618 current non‐smokers (P < 0.0001). Similar associations between smoking and the early diagnosis of upper tract urothelial carcinoma were shown in the sex subgroups and in subgroups stratified by pathological T stages. Among the current smokers, the age at diagnosis for the smoking ≥ 20 cigarettes per day group was 6.5 years lower than that of the < 20 cigarettes per day group, which was significantly different (P < 0.0001). Conclusion Current smoking is a significant risk factor for the earlier diagnosis of upper tract urothelial carcinoma. The finding is important from the perspective of both healthcare and medical economies.